2019
DOI: 10.3390/nu11040821
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Extracts Attenuate Brain Dysfunction in High-Fat-Diet-Fed SAMP8 Mice

Abstract: Unhealthy diet promotes progression of metabolic disorders and brain dysfunction with aging. Green tea extracts (GTEs) have various beneficial effects and alleviate metabolic disorders. GTEs have neuroprotective effects in rodent models, but their effects against brain dysfunction in models of aging fed unhealthy diets are still unclear. Here, we showed that GTEs attenuate high-fat (HF) diet-induced brain dysfunction in senescence-accelerated mouse prone-8 (SAMP8), a murine model of senescence. SAMP8 mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…For instance, the extracts from green tea, a Japanese traditional drink, improved brain dysfunction induced by high fat diet in senescence-accelerated mouse prone-8 (SAMP8) mice. Brain histological change, such as amyloid β accumulation or the reduction of brain-derived neurotrophic factor (BDNF), was suppressed with the diet including this extract [25]. In a primary culture of murine cortical neurons, administration of polyphenol-enriched extracts induced epigenetic change resulting in the cellular protection [26].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the extracts from green tea, a Japanese traditional drink, improved brain dysfunction induced by high fat diet in senescence-accelerated mouse prone-8 (SAMP8) mice. Brain histological change, such as amyloid β accumulation or the reduction of brain-derived neurotrophic factor (BDNF), was suppressed with the diet including this extract [25]. In a primary culture of murine cortical neurons, administration of polyphenol-enriched extracts induced epigenetic change resulting in the cellular protection [26].…”
Section: Discussionmentioning
confidence: 99%
“…This might promote morphology and spine density in neuronal cells, thereby enhancing learning and memory function. In addition, treatment with green tea catechins ameliorated memory impairments and promoted spatial learning function by diminishing the oligomers of Aβ (1–42) in senescence-accelerated mice by augmenting the expression of the PKA/CREB pathway in the hippocampus [ 64 ]. Furthermore, EGCG promoted ERK and PI3K-mediated phosphorylation of CREB as well as stimulated GluR2 levels and modulated synaptogenesis, neurotransmission activity, and plasticity in cortical neurons [ 65 ].…”
Section: Phytochemicals Prevent Mitochondrial Dysfunction and Imprmentioning
confidence: 99%
“…Besides, previous studies have revealed that there was significant microglia activation after HFD 18,19 . Microglia activation plays an important role in the development of neurobehavioral deficits caused by HFD 20,21 . Studies have found that the aggregation and activation of microglia can be detected in most central neurodegenerative diseases 22 .…”
Section: Introductionmentioning
confidence: 97%